Estudo do concreto de alto desempenho com adição de agregados reciclados - Santos, Jocileila Lima (2021)
Civil construction has been improving its construction techniques and as a consequence came the technological advancement that is now widespread in the world. Along with the advancement in the sector and in construction techniques, there was also an increase in the consumption of natural resources and a marked generation of waste. In search of sustainable development, there is a need to use components in construction that minimize the use of natural resources. Concrete is widely used, and in the evolution of concrete technology, high performance concrete arises. High performance concrete has been increasingly used in civil construction, in addition to being the object of study considering the complexity of reaching high strengths. This search is justified by the several benefits that this material allows, among them are the high mechanical resistance and excellent durability, which results in a reduction in the sections of compressed parts and gain of useful area. The study is notorious in order to clarify doubts about the optimum content of additive, water / cement ratio, consumption of cement and aggregates that provide adequate workability to concrete in the fresh state and excellent properties to hardened concrete. In this work, a study of the constituent materials of high performance concrete was developed, suggesting the use of recycled aggregate from marble and granite cutting and processing residues as partial replacement of fine aggregates in the dosage.